Michael Jordan the life - Lazenby, Roland (New York, NY Little, Brown and Company, 2014)
Traces the life of one of the most legendary basketball players in the history of the sport, drawing upon interviews with Jordan's friends, family, and teammates, and following his career from college to the NBA.
pt. I. Cape Fear : Holly Shelter ; Bloody Wilmington -- pt. II. Early times : The influence ; The competitor ; The diamond -- pt. III. Emergence : The cut ; Number 23 ; The transformation ; The five-star ; The Michael -- pt. IV. True blue : The freshman ; Something new ; System failure -- pt. V. The rookie : Gold rush ; Black power ; The first look -- pt. VI. Flight school : The young prisoner ; The foot ; Attack! -- pt. VII. Cynic : That's entertainment ; Ruling Jordan ; Flying high and dry ; The drive-by wedding ; The transition ; The god of basketball -- pt. VIII. Something gained : Triangular ; The gamble ; All that glitters -- pt. IX. Far and away : The Lexus ; The diamond dream ; Come again ; Training camp -- pt. X. Fury : The carnival ; The reckoning ; Firing up the bus -- pt. XI. The afterlife : Limbo ; The wizard ; Carolina
Includes bibliographical references (pages 679-691) and index.
Keywords: Jordan, Michael -- 1963-.; Chicago Bulls (Basketball team) .; Basketball players -- United States -- Biography